Design and fabrication of foldable chair - Maaruf, Muhamad (2007)
Idea to design and fabricate a foldable chair is come from a supervisor that gives a task and a title for this project. To design and fabricate this foldable chair it must compare with the other product that available in market. To make sure the idea to design and fabricate the foldable chair is not used and in old idea, the information about current design for foldable chair must search or get from the internet. Form there the information and idea to design and fabricate a foldable can be created. It includes many things about foldable chair design that wanted to know. Whole of the project involve various methods like the concept design, the designing and also the fabrication process. Beside that in this project can bring a motivation and experience to conduct the various type of machine, train to work under the pressure, and also soft skill ability like time management,planning the task, negotiation skill and sell Out the idea especially during work progress presentation.